Pea ferritin stability under gastric pH conditions determines the mechanism of iron uptake in caco-2 cells - Perfecto, Antonio; Rodriguez-Ramiro, Ildefonso; Rodriguez-Celma, Jorge; Sharp, Paul; Balk, Janneke; Fairweather-Tait, Susan J. (Oxford University Press, 2018)
Iron deficiency is an enduring global health problem that requires new remedial approaches. Iron absorption from soybean-derived ferritin, an ∼550-kDa iron storage protein, is comparable to bioavailable ferrous sulfate (FeSO4). However, the absorption of ferritin is reported to involve an endocytic mechanism, independent of divalent metal ion transporter 1 (DMT-1), the transporter for nonheme iron.